Analisis Spatiotemporal Dinamika Garis Pantai Dan Pemetaan Zona Bahaya Tsunami Di Kota Padang Menggunakan Penginderaan Jauh dan Sistem Informasi Geografis - Faizah Musra; Elistia Liza Namigo (Jurnal Fisika Unand, 2026)
The city of Padang is one of Indonesia's coastal areas that is highly vulnerable to tsunamis due to its location directly facing the Mentawai–Sumatra megathrust subduction zone. This study aims to analyze coastal dynamics using multitemporal satellite imagery and examine its relationship with tsunami hazard zoning based on the physical characteristics of the area. The methodology includes digitizing the coastline for 2013 and 2025, analyzing the rate of coastline change using the Digital Shoreline Analysis System (DSAS), and combining spatial parameters such as elevation, slope, distance from the coastline, and proximity to rivers to produce a tsunami hazard zone map. Overlay analysis indicates that areas with low elevation, gentle slopes, and proximity to river mouths and coastlines fall into the category of high tsunami vulnerability. The results of the study show spatial variations in coastal dynamics in Padang City, with significant abrasion observed in Koto Tangah District (-1.754 m/year) and Padang Selatan (-1.051 m/year), while notable accretion was recorded in Bungus Teluk Kabung (+1.470 m/year). This study proves that the integration of remote sensing data and Geographic Information Systems (GIS) provides a comprehensive spatial framework to support coastal disaster mitigation efforts and risk-based spatial planning.